Creating a familiar space: Childcare, kinship and community in Post-socialist New Zagreb - Rubić, Tihana (Array, 2015)
The paper offers insights into ethnographic field research on narratives and everyday experiences of childcare assistance by inhabitants of Novi Zagreb’s urban settlement Travno. The settlement was built in the early 1970s as part of the southern suburb of Zagreb and as a middle and working class residential area. The chosen field site serves as an example of a contemporary urban settlement’s network and its embeddedness into changing social, political, and welfare policies over thirty years of its existence, including the transition from a socialist to a (neo-)liberal and democratic system. The chapter focuses on kinship and neighborhood as two relevant social frames in providing everyday assistance in the settlement, with a particular emphasis on the role of childcare. It shows that in socialism, inhabitants turned neighbours into kin in order to provide family like childcare while relatives would live in distance. In postsocialism, next to these neighbourly relations proximity of two kin related households, first of all those of a young couple and their parents (in law), could be established. Kin related households built localized family networks of child care and solidarity which enabed young mothers to take up or continue wage work and therewith to cope with the new challenges of the neo-liberalized market economy.. In this way especially the role of neighbours and locally present grandmothers as prominent childcare givers will be examined.